Mycorrhizal extraradical mycelium can reduce cadmium uptake by maize and cadmium leaching from contaminated soil: based on an in-growth core experiment - Yang, Yijie; Li, Yang; Li, Xiaoyi; Yan, Jie; Wu, Longhua; Tang, Zhenwu; He, Yongmei; Zhan, Fangdong (Frontiers in Microbiology, 2024)
Arbuscular mycorrhizal fungi (AMF) are commonly found in heavy metal-contaminated environments and form extraradical mycelium (ERM), but knowledge of their ecological functions is limited. In the present study, a soil column was filled with sterilized cadmium (Cd)-contaminated soil and contained an in-growth core for AMF-inoculated maize seedling growth. The in-growth core was static to maintain or rotated to disrupt ERM growth. Compared with the static treatment, the rotation treatment caused significant decreases in the content of glomalin-related soil protein (GRSP), the photosynthetic physiology of leaves, and maize growth, while increasing the Cd content in shoots and roots by 64 and 82%, respectively; additionally, the rotation treatment resulted in increases in the Cd concentration of the soil solution inside and outside the growth core by 30–38 and 17–52%, respectively, and Cd leaching loss by 29–39%. Moreover, the rotation treatment significantly altered the Cd forms in the soil solution and leachate, increasing the proportion of free Cd2+ by 0.8–2.1% and decreasing the proportions of CdSO4(aq) and CdOH+ by 6.1–56.1% and 26.1–48.7%, respectively. The structural equation model indicated that AMF directly and indirectly reduced maize Cd uptake and Cd leaching loss by decreasing Cd availability in the soil and soil solution through the GRSP secreted by ERM. Thus, AMF plays a crucial role in inhibiting Cd migration in soil through mycelial exudates.